OPTIMALISASI PERKEMBANGAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB MELALUI PEMBELAJARAN BERBASIS PROYEK: Optimalisasi Perkembangan Karakter Disiplin dan Tanggung Jawab Peserta Didik Sekolah Dasar melalui Pembelajaran Berbasis Proyek - Faisal, Vava Imam Agus; Apriliani, Elina Intan; Agustin, Alfiana (jsd: Journal of Society and Development, 2025)
Project-Based Learning (PjBL) serves as an effective strategy for developing students’ discipline and responsibility while strengthening the core values of the Profil Pelajar Pancasila within the Merdeka Curriculum framework. This study aims to describe the implementation of PjBL in fostering disciplined and responsible character among students at SDN Kebrengan and to analyze its impact on reinforcing the values of the Profil Pelajar Pancasila. Employing a qualitative approach with observation, interview, and documentation techniques, the study found that PjBL effectively nurtures students’ discipline, responsibility, collaboration, and independence through contextual project activities such as creating learning tools from recycled materials. The model not only enhances academic skills but also serves as an effective medium for instilling moral and social values through reflective learning experiences. Despite challenges such as varying levels of student independence and time limitations, PjBL aligns with the spirit of the Merdeka Curriculum that emphasizes meaningful learning. In conclusion, PjBL contributes significantly to strengthening students’ discipline and responsibility while serving as a strategic alternative for promoting the Profil Pelajar Pancasila in elementary education.